Before it is too late: professional responsibilities in late-onset Alzheimer’s research and pre-symptomatic prediction - Schicktanz, Silke; Schweda, Mark; Ballenger, Jesse F.; Fox, Patrick J.; Halpern, Jodi; Kramer, Joel H.; Micco, Guy; Post, Stephen G.; Thompson, Charis; Knight, Robert T.; Jagust, William J. (Frontiers in Human Neuroscience, 2014)
The development of a wide array of molecular and neuroscientific biomarkers can provide the possibility to visualize the course of Alzheimer’s disease (AD) at early stages. Many of these biomarkers are aimed at detecting not only a preclinical, but also a pre-symptomatic state. They are supposed to facilitate clinical trials aiming at treatments that attack the disease at its earliest stage or even prevent it. The increasing number of such biomarkers currently tested and now partly proposed for clinical implementation calls for critical reflection on their aims, social benefits and risks. This position paper summarizes major challenges and responsibilities. Its focus is on the ethical and social problems involved in the organization and application, of dementia research as well as in health care provision from a cross-national point of view. The paper is based on a discussion of leading dementia experts from various disciplines, such as neuroscience, neurology, social sciences, and bioethics. We intend to initiate a debate on the need for actions within the researchers’ national and international communities.